2021
DOI: 10.3390/nu13030849
|View full text |Cite
|
Sign up to set email alerts
|

Re-Defining the Population-Specific Cut-Off Mark for Vitamin A Deficiency in Pre-School Children of Malawi

Abstract: Retinol Binding Protein (RBP) is responsible for the transport of serum retinol (SR) to target tissue in the body. Since RBP is relatively easy and cheap to measure, it is widely used in national Micronutrient Surveys (MNS) as a proxy for SR to determine vitamin A status. By regressing RBP concentration against SR concentration measured in a subset of the survey population, one can define a population-specific threshold concentration of RBP that indicates vitamin A deficiency (VAD). However, the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The prevalence of vitamin A deficiency in this study was higher (21%) than that previously reported in the general population of children under five years in Africa. Vitamin A deficiency was estimated at 8.9% (RBP < 0.8 µmol/L) in Uganda [27], 9.2% (RBP < 0.7 µmol/L) in Kenya [28], and 10% (RBP < 0.7 µmol/L) in Malawi [29]. Additionally, a cross-sectional study in Uganda found that low S-RBP (<0.8 µmol/L) was associated with higher odds of stunting in children aged 6-59 months [27].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vitamin A deficiency in this study was higher (21%) than that previously reported in the general population of children under five years in Africa. Vitamin A deficiency was estimated at 8.9% (RBP < 0.8 µmol/L) in Uganda [27], 9.2% (RBP < 0.7 µmol/L) in Kenya [28], and 10% (RBP < 0.7 µmol/L) in Malawi [29]. Additionally, a cross-sectional study in Uganda found that low S-RBP (<0.8 µmol/L) was associated with higher odds of stunting in children aged 6-59 months [27].…”
Section: Discussionmentioning
confidence: 99%
“…38 Recent evidence suggests that the combination of vitamin A fortification and supplementation interventions may be leading to excessive vitamin A intake among PSC in Malawi, 18 although caution is needed in interpreting these data and more research is needed before consideration of any policy changes. 39,40 We found a low risk of excessive vitamin A intakes under the status quo fortification scenario, although the risk of excessive apparent intake increases to 19% among wealthy, urban households under the improved compliance scenario (Table S5, online only). Further research is needed to model how additional micronutrient interventions can meet vitamin A needs unaddressed by oil and sugar fortification.…”
Section: Oil and Sugar Fortificationmentioning
confidence: 88%
“… 6 , 38 , 45 The national burdens of micronutrient deficiencies are classified using biomarker surveys, but operational and analytical challenges can pose difficulties when interpreting results. 40 Furthermore, some micronutrients that were indicated by this analysis to be of concern for dietary inadequacy are either not commonly assessed using biomarker analyses (e.g., riboflavin) or are challenging to measure using biomarkers, for example, owing to tight homeostatic control of concentrations in blood plasma/serum (e.g., zinc). 46 Using dietary data to assess inadequacies in micronutrient intake can provide information to guide the design of policies centered around food‐based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, efforts should be made to ensure transparency and collaboration among researchers, which would facilitate data sharing, harmonisation, and ultimately contribute to more accurate estimates of VAD burden globally. Second, Vitamin A is stored in the liver and transported to the end organs by retinol binding protein (RBP) [24]. Therefore, circulating concentrations of RBP, the carrier protein for serum (plasma) retinol, are also considered a biological indicator of VAD in some large investigations [25].…”
Section: Discussionmentioning
confidence: 99%